Assessment of the condition of the multifunctional green area of Voronezh “Park named after Sherstyuk” - Kharchenko Nikolay; Matytsina Elizaveta; Prokhorova Nadezhda; Kirillova Elizaveta (BIO Web of Conferences)
The article is devoted to the current environmental problem of the urban environment - the presence and condition of public green areas. The article presents the results of an environmental assessment of the state of the multifunctional green area of the city of Voronezh “Park named after. Sherstyuk.” The main goal was to determine the qualitative and quantitative state of tree plantations by species, as well as an inventory of emissions from vehicles to determine the state of ground-level atmospheric air. When conducting research, standard methods of environmental research were used, followed by desk processing. The tables below reflect data on the species composition, average diameter and height of plantings, as well as the number of tree species by condition category. The tables also reflect the content of harmful substances in the atmospheric air, calculated in accordance with GOST R 56162-2014.